PENGEMBANGAN SISTEM KOMUNIKASI DARURAT PORTABEL BERBASIS STARLINK DAN PANEL SURYA UNTUK DUKUNGAN OPERASI SAR KEBENCANAAN - Hari Jalsa Marpaung; Andrew Ramadhani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Hydrometeorological disasters frequently damage electrical and telecommunication infrastructures, disrupting the coordination of Search and Rescue (SAR) operations. Conventional communication devices such as Handy Talkies (HT) are limited to voice communication and do not support real-time multimedia data transmission. This study aims to develop a portable emergency communication system based on Low Earth Orbit (LEO) Starlink satellite internet integrated with a solar power system as an independent energy source to support communication during post-disaster emergency response. The research employs the Research and Development (R&D) approach using the Design Science Research (DSR) paradigm, consisting of requirement identification, system architecture design, prototype development, laboratory testing, and field simulation. System performance is evaluated based on Quality of Service (QoS) parameters, including latency, throughput, connection stability, power consumption, operating duration, and system portability. The prototype is designed to weigh less than 15 kg, require less than 10 minutes for deployment, and operate independently for 6–8 hours using a 300–500 W solar power system. The proposed system is expected to provide reliable internet connectivity for real-time transmission of audio, video, images, and GPS coordinates, thereby improving the effectiveness of SAR coordination in disaster-affected areas. Keywords: Emergency Communication; Starlink; Solar power; Search and Rescue; Satellite Network.   Abstrak: Bencana hidrometeorologi sering menyebabkan kerusakan infrastruktur listrik dan telekomunikasi sehingga menghambat koordinasi operasi Search and Rescue (SAR). Keterbatasan perangkat komunikasi konvensional seperti Handy Talky (HT) mengakibatkan pertukaran informasi hanya terbatas pada komunikasi suara tanpa dukungan data multimedia secara real-time. Penelitian ini bertujuan mengembangkan sistem komunikasi darurat portabel berbasis internet satelit Low Earth Orbit (LEO) Starlink yang terintegrasi dengan panel surya sebagai sumber energi mandiri untuk mendukung komunikasi pada kondisi pascabencana. Metode penelitian menggunakan pendekatan Research and Development (R&D) dengan paradigma Design Science Research (DSR) yang meliputi identifikasi kebutuhan, perancangan arsitektur sistem, pengembangan prototipe, pengujian laboratorium, dan simulasi lapangan. Evaluasi dilakukan terhadap parameter Quality of Service (QoS) berupa latensi, throughput, stabilitas koneksi, konsumsi daya, durasi operasi, serta portabilitas sistem. Prototipe dirancang berbobot kurang dari 15 kg, waktu pemasangan kurang dari 10 menit, dan mampu beroperasi mandiri selama 6–8 jam menggunakan panel surya berkapasitas 300–500 W. Sistem yang dikembangkan diharapkan mampu menyediakan konektivitas internet yang stabil untuk mendukung komunikasi audio, video, citra, dan koordinat GPS secara real-time, sehingga meningkatkan efektivitas koordinasi operasi SAR di wilayah terdampak bencana.. Kata kunci: Komunikasi darurat; Starlink; Panel Surya; Search and Rescue; Jaringan Satelit.